Application of Distributed Optical Fiber Technology for Coal Bump Prevention. (9th July 2021) - Liang, Han; Han, Jun; Bi, Zuoqing
Abstract : The 8939 working face in Xinzhouyao coal mine is a high coal bump proneness panel. For coal bump prevention, rib holes are drilled for pressure relief purpose. The deformational behaviour of the pressure relief borehole is studied using distributed optical fiber sensing technology. The strain of the surrounding coal and the pressure relief range were measured from 0 hrs to 402 hrs after hole drilling. Based on the analysis of pressure relief procedure, combining with borehole observation, the crack development, limited equilibrium, collapse, and compaction stages of the borehole were estimated as 0∼72 h, 72∼190 h, 190∼402 h, and greater than 402 h, respectively. Consequently, the hole drilling is modified to 110 m ahead of the working face to achieve better pressure relief effect. Microseismic monitoring shows that, after hole drilling optimisation, the high-energy microseismic events and average energy of microseismic events are reduced significantly.